2014
DOI: 10.3892/mmr.2014.2400
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of connexin43 in the acute hyperosmotic stimulus-induced synthesis and release of vasopressin in the supraoptic nucleus of rats

Abstract: Abstract. There is evidence that astroglial connexin43 (Cx43) in the supraoptic nucleus (SON) is required for the hyperosmolarity-induced increase in Fos protein expression in magnocellular neurosecretory cells (MNCs). In the present study, the role of astroglial Cx43 in the synthesis and release of vasopressin (VP) by MNCs in the SON subjected to hyperosmotic stimulus was examined. The results revealed that the VP levels in the SON and plasma were increased following acute hyperosmotic stimulus. Treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have revealed the presence of Cx32 in SON neurons and Cx43 in SON astrocytes (Micevych et al., 1996). VP synthesis and release induced by hyperosmotic stimulation depend on increased expression of Cx43 and its function in the SON (Jiang et al., 2014). In this study, we provide the evidence of Cx36 presence in SON neurons based on studies using immunohistochemistry, Western blotting, and electrophysiology, thereby allowing a new venue to explore the biological functions of gap junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed the presence of Cx32 in SON neurons and Cx43 in SON astrocytes (Micevych et al., 1996). VP synthesis and release induced by hyperosmotic stimulation depend on increased expression of Cx43 and its function in the SON (Jiang et al., 2014). In this study, we provide the evidence of Cx36 presence in SON neurons based on studies using immunohistochemistry, Western blotting, and electrophysiology, thereby allowing a new venue to explore the biological functions of gap junctions.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, hemichannels mediate the release of signaling molecules from cells such as ATP [6], glutamate [7], reduced glutathione (GSH) [8,9], and nicotinamide adenine dinucleotide (NAD + ) [10] as well as the uptake of glucose [11] and Ca 2+ [12]. Due to their permeability to second messengers and metabolites, hemichannels participate in relevant physiological functions, such as the formation of short-term memory [13], memory consolidation [14], gliotransmitter release [15], retina function [16], bone-hormone response and healing [17,18], neuronal-network activity [19], vasopressin synthesis and release [20], CO 2 sensing [21], etc. Despite these roles, it is well known that hemichannels present a low open probability under physiological conditions [22], which is greatly increased under pathological conditions [23,24] including metabolic stress [25], ischemia [26], inflammation [11], deafness [27], X-linked Charcot-Marie-Tooth disease [28], and skin diseases [29].…”
Section: Introductionmentioning
confidence: 99%